Case Analysis of Generative AI Adoption and Application Based on the UTAUT Theory: Taking Ctrip's TripGenie Intelligent Travel Chatbot as an Example - Sun, Dongshuo; Leong, Wai Yie (INTI International University, 2025)
This study takes TripGenie, an intelligent travel chatbot jointly developed by Trip.com (affiliated with Ctrip) and Microsoft, as a case study. Combined with the core framework of the Unified Theory of Acceptance and Use of Technology (UTAUT), it systematically analyzes the adoption logic and application value of Generative Artificial Intelligence (GenAI) in the tourism industry. The research findings indicate that the successful adoption of TripGenie stems from its accurate matching of the performance needs of both users and enterprises, reduction of technical usage thresholds, diffusion relying on industry demonstration effects, and formation of enabling conditions through the integration of resources from both parties. Ultimately, it achieves the upgrading of user experience, business growth, and optimization of operational efficiency